PARP-inhibitors for BRCA1/2-related advanced HER2-negative breast cancer: A meta-analysis and GRADE recommendations by the Italian Association of Medical Oncology. (December 2022) - Miglietta, Federica; Cinquini, Michela; Dieci, Maria Vittoria; Cortesi, Laura; Criscitiello, Carmen; Montemurro, Filippo; Del Mastro, Lucia; Zambelli, Alberto; Biganzoli, Laura; Levaggi, Alessia; Delle Piane, Chiara; Marchiò, Caterina; et al.
Abstract: Background: Approximately 5–10% of unselected breast cancer (BC) patients retain a hereditary predisposition related to a germline mutation in BRCA1/2 genes. The poly-ADP ribose polymerase (PARP)-inhibitors olaparib and talazoparib have been granted marketing authorization by both FDA and EMA for adults with BRCA1/2 germline mutations and HER2-negative (HER2-) advanced BC based on the results from the phase III OlympiAd and EMBRACA trials. Methods: The panel of the Italian Association of Medical Oncology (AIOM) Clinical Practice Guidelines on Breast Cancer addressed two critical clinical questions, adopting the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach and the Evidence to Decision framework (EtD), to develop recommendations on the use of PARP-inhibitors, with respect to single-agent chemotherapy, in patients with BRCA-related triple-negative (clinical question 1) and hormone receptor-positive (HR+)/HER2- (clinical question 2) advanced BC. Results: Two studies were eligible (OlympiAd and EMBRACA). For both clinical questions, the Panel judged the benefit/harm balance probably in favor of the intervention, given the favorable impact in terms of PFS, ORR, and QoL at an acceptable cost in terms of toxicity; the overall certainty of the evidence was low. The panel's final recommendations were conditional in favor of PARP-inhibitors over single-agent chemotherapy in both HR+/HER2-and triple-negative BC. Finally, the Panel identified and discussed areas of uncertainty calling for further exploration. Conclusions: The Panel of AIOM BC Clinical Practice Guideline provided clinical recommendations on the use of PARP-inhibitors, with respect to single-agent chemotherapy, in patients with BRCA-related HER2-advanced BC by adopting the GRADE methodology. Highlights: Use of PARP-inhibitors in BRCA-related HER2-advanced BC has been addressed by the Italian Association of Medical Oncology. The Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach has been adopted. HR+/HER2-and triple-negative BC subtypes have been addressed in two separate clinical questions. Germline BRCA testing in HER2-advanced BC has a predictive value, being indicated independently from familial criteria.